ANALYSIS OF THE PROCESS OF ISSUING A SAILING APPROVAL LETTER ON THE INAPORTNET APPLICATION AT THE OFFICE OF THE PORT MASTER AND CLASS I BITUNG PORT AUTHORITY - Dacroun Larson Wongkar; Jetty E. H. Mokat; Goinpeace Tumbel (PT. Radja Intercontinental Publishing, 2026)
This study aims to analyze and describe the Sailing Approval Letter issuance service and identify inhibiting factors in the Sailing Approval Letter issuance service at the Bitung Class I Harbormaster and Port Authority Office. This study uses a qualitative research method with a descriptive approach. Data collection was conducted through observation, interviews, and documentation. Research informants consisted of officials and officers of the Bitung Class I KSOP and users of the SPB issuance service. Data analysis was carried out through the stages of data reduction, data presentation, and conclusion drawing. The results of the study indicate that the Sailing Approval Letter issuance service at the Bitung Class I KSOP has not been running optimally because various obstacles are still encountered. The inhibiting factors found include the stability of the electronic service system that does not fully support smooth operations due to network disruptions, delays in data synchronization, and unstable server performance; the capacity of human resources to adapt to digital-based services that is still not optimal, resulting in frequent data input errors and document discrepancies; and support for information technology infrastructure and coordination between service units that have not been implemented in an integrated manner, thus affecting the effectiveness and speed of the SPB issuance service. The conclusion of this study shows that the implementation of INAPORTNET-based SPB issuance services at KSOP Class I Bitung has supported the modernization of maritime public services, but its effectiveness is still influenced by technical factors, human resources, and institutional coordination.